2019
DOI: 10.1007/s12471-019-01318-8
|View full text |Cite
|
Sign up to set email alerts
|

Global longitudinal strain to predict left ventricular dysfunction in asymptomatic patients with severe mitral valve regurgitation: literature review

Abstract: The optimal treatment strategy for asymptomatic patients with severe mitral valve regurgitation (MR) and preserved left ventricular (LV) function is challenging. This manuscript reviews the available literature on the value of left ventricular global longitudinal strain (LV-GLS) in predicting LV dysfunction after mitral valve surgery in these patients and discusses its current place in the treatment strategy. Studies were identified from Cochrane Library, SCO-PUS, PubMed and Web of Science up to February 2018.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 30 publications
0
22
0
Order By: Relevance
“…LV ejection fraction is one of these postoperative parameters, but because of its shortcoming of being loaddependent, LV-GLS has been introduced as another method of assessing LV function. Although LV-GLS measurement is associated with a significant learning curve, 6 it may add important information on LV function, especially in asymptomatic patients 7 and in synergy with other parameters. 8 The use of other potential surrogates of long-term clinical outcomes that require further investigation include biomarkers, LV volume measurements, and modern imaging tools (eg, myocardial fibrosis in magnetic resonance imaging).…”
Section: Thismentioning
confidence: 99%
“…LV ejection fraction is one of these postoperative parameters, but because of its shortcoming of being loaddependent, LV-GLS has been introduced as another method of assessing LV function. Although LV-GLS measurement is associated with a significant learning curve, 6 it may add important information on LV function, especially in asymptomatic patients 7 and in synergy with other parameters. 8 The use of other potential surrogates of long-term clinical outcomes that require further investigation include biomarkers, LV volume measurements, and modern imaging tools (eg, myocardial fibrosis in magnetic resonance imaging).…”
Section: Thismentioning
confidence: 99%
“…Early surgery in severe MR patients is associated with preserved left ventricular function and lower incident heart failure risk (38,39). Bijvoet et al made a literature review about usefulness of LV-GLS in asymptomatic MR patients (40). They found that an impaired LV-GLS (range: -17.9 and -21.7%) is a predictor of both left ventricular dysfunction and an increased mortality (40).…”
Section: C) Lv-gls In Mitral Regurgitationmentioning
confidence: 99%
“…Hebden and Torry [7] projected a method for distinguishing the systolic murmurs arising from aortic stenosis and MV regurgitation by the computation of frequency contents. Bijvoet et al [8] has discussed about the literature survey on optimal strategies for predicting severe mitral valve regurgitation on patients after surgery as well as global longitudinal left ventricular dysfunction. Bruscoand Nazeran [9] discussed an intelligent PDA dependent wearable digital phonocardiograph that could not save the heart sounds; however, diverse signal processing and statistical approaches are employed to segment the signals into a set of four parts, namely, S1, systole, S2 and diastole.…”
Section: Review Criteriamentioning
confidence: 99%